The Neonatal Outcomes and resuscitation rate of Neonates at Imam Reza Hospital, Mashhad, Iran - AhmadShah Farhat; Fatemeh Chitgar Rahimi; Ashraf Mohammadzade; Reza Saeedi; Mozhgan Ghiassi; Jamileh Omidbigi; Fatemeh Qadernia (Mashhad University of Medical Sciences, 2020)
Background & aim: Neonatal mortality rate (NMR) is an important health index, which reflects the socio-economic and health status of a community. According to the literature, almost 20% of NMR can be prevented through the implementation of simple resuscitative interventions. This study was conducted to review the neonatal outcomes and resuscitation rate of neonates. Methods: This record review was carried out using records of 4683 birth from March 2016 to March 2017 in Imam Reza Hospital, Mashhad, Iran. The variables reviewed included the birth conditions, neonatal outcomes and resuscitation interventions. The data were collected using a self-structured record form and analyzed using descriptive statistics. Results: The findings showed 179 neonatal deaths out of 4683 births (including those who were born dead or the ones who died shortly after birth in delivery rooms). NMR was 3.8% in the current study. The rate of cesarean deliveries was 5% higher than normal vaginal delivery rate. Moreover, 18% of births were related to the gestational age lower than 36 weeks. The rate of low and very low birth weight infants was 6.42% of births. Approximately, 20% of the newly born infants were resuscitated. Conclusion: The results of this study revealed that Imam Reza Hospital of Mashhad, Iran was not in a good condition compared to the developed countries, in terms of the status of births, mortality rate, and resuscitation interventions.Background & aim: Neonatal mortality rate (NMR) is an important health index, which reflects the socio-economic and health status of a community. According to the literature, almost 20% of NMR can be prevented through the implementation of simple resuscitative interventions. This study was conducted to review the neonatal outcomes and resuscitation rate of neonates. Methods: This record review was carried out using records of 4683 birth from March 2016 to March 2017 in Imam Reza Hospital, Mashhad, Iran. The variables reviewed included the birth conditions, neonatal outcomes and resuscitation interventions. The data were collected using a self-structured record form and analyzed using descriptive statistics. Results: The findings showed 179 neonatal deaths out of 4683 births (including those who were born dead or the ones who died shortly after birth in delivery rooms). NMR was 3.8% in the current study. The rate of cesarean deliveries was 5% higher than normal vaginal delivery rate. Moreover, 18% of births were related to the gestational age lower than 36 weeks. The rate of low and very low birth weight infants was 6.42% of births. Approximately, 20% of the newly born infants were resuscitated. Conclusion: The results of this study revealed that Imam Reza Hospital of Mashhad, Iran was not in a good condition compared to the developed countries, in terms of the status of births, mortality rate, and resuscitation interventions.